Research Progress of Biosimilars of Monoclonal Antibody Drugs For The Treatment of Tumors - Qian, Jiahao (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Monoclonal antibodies (mAbs) have gained prominence in cancer treatment due to their targeted therapeutic mechanisms, offering fewer side effects compared to traditional chemotherapy. Despite the advancement in original mAb-based anticancer drugs, the high costs associated with these therapies pose a significant challenge, especially for low- and middle-income countries. This has led to an increased focus on developing biosimilars, which are more affordable alternatives with similar therapeutic effects. This paper reviews the research progress of mAb drugs and their biosimilars for tumor treatment, highlighting the clinical impact of mAbs targeting common cancer markers such as HER-2, CD38, and eEF2K. For instance, trastuzumab biosimilars have been shown to improve the pathological complete response rate (pCR) in breast cancer patients when added to neoadjuvant chemotherapy, demonstrating an approximate 15% increase compared to chemotherapy alone. The study concludes that while biosimilars provide a cost-effective and accessible alternative, there is still a lack of long-term clinical data and real-world efficacy, particularly for biosimilars targeting newer cancer markers like CD38 and eEF2K. The paper highlights key advancements in biosimilar production, such as those of trastuzumab biosimilars, and discusses emerging targets like eEF2K, with potential for future therapeutic interventions.